Cytokine networking of innate immunity cells: a potential target of therapy - Striz, Ilja; Brabcova, Eva; Kolesar, Libor; Sekerkova, Alena (Clinical science (London, England, 2014)
Innate immune cells, particularly macrophages and epithelial cells, play a key role in multiple layers of immune responses. Alarmins and pro-inflammatory cytokines from the IL (interleukin)-1 and TNF (tumour necrosis factor) families initiate the cascade of events by inducing chemokine release from bystander cells and by the up-regulation of adhesion molecules required for transendothelial trafficking of immune cells. Furthermore, innate cytokines produced by dendritic cells, macrophages, epithelial cells and innate lymphoid cells seem to play a critical role in polarization of helper T-cell cytokine profiles into specific subsets of Th1/Th2/Th17 effector cells or regulatory T-cells. Lastly, the innate immune system down-regulates effector mechanisms and restores homoeostasis in injured tissue via cytokines from the IL-10 and TGF (transforming growth factor) families mainly released from macrophages, preferentially the M2 subset, which have a capacity to induce regulatory T-cells, inhibit the production of pro-inflammatory cytokines and induce healing of the tissue by regulating extracellular matrix protein deposition and angiogenesis. Cytokines produced by innate immune cells represent an attractive target for therapeutic intervention, and multiple molecules are currently being tested clinically in patients with inflammatory bowel disease, rheumatoid arthritis, systemic diseases, autoinflammatory syndromes, fibrosing processes or malignancies. In addition to the already widely used blockers of TNFα and the tested inhibitors of IL-1 and IL-6, multiple therapeutic molecules are currently in clinical trials targeting TNF-related molecules [APRIL (a proliferation-inducing ligand) and BAFF (B-cell-activating factor belonging to the TNF family)], chemokine receptors, IL-17, TGFβ and other cytokines.
Keywords: signální transdukce; Immunity, Innate; Signal Transduction; Adaptive Immunity; Humans; antiflogistika; imunitní systém; cytokiny; Antineoplastic Agents; Immune System; lidé; zvířata; imunosupresiva; Immunosuppressive Agents; adaptivní imunita; Cytokines; protinádorové látky; Anti-Inflammatory Agents; Animals; Inflammation Mediators; mediátory zánětu; přirozená imunita